2020
DOI: 10.1186/s12885-020-06806-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of alpha-fetoprotein in patients with hepatocellular carcinoma treated with repeat transarterial chemoembolisation

Abstract: Background: Repeat transarterial chemoembolisation (rTACE) is often required for hepatocellular carcinoma (HCC) to achieve disease control, however, current practice guidelines regarding treatment allocation vary significantly. This study aims to identify key factors associated with patient survival following rTACE to facilitate treatment allocation and prognostic discussion. Method: Patients with HCC undergoing rTACE at six Australian tertiary centers from 2009 to 2014 were included. Variables encompassing cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…After PSM, multivariate analysis in the Ki67 low expression group showed that a preoperative AFP level >200mg/liter (13) and a tumor maximum diameter ≥5 cm (14) were independent risk factors for RFS and OS rates in patients post-operatively, and liver cirrhosis was an independent risk factor for RFS (HR = 3.50 and 2.58, P = 0.001 and 0.015, respectively; and HR = 4.10 and 2.79, P = 0.006 and 0.041, respectively; and HR = 2.39, P = 0.02).…”
Section: Multivariate Analysis On Recurrence and Survival Of Patientsmentioning
confidence: 99%
“…After PSM, multivariate analysis in the Ki67 low expression group showed that a preoperative AFP level >200mg/liter (13) and a tumor maximum diameter ≥5 cm (14) were independent risk factors for RFS and OS rates in patients post-operatively, and liver cirrhosis was an independent risk factor for RFS (HR = 3.50 and 2.58, P = 0.001 and 0.015, respectively; and HR = 4.10 and 2.79, P = 0.006 and 0.041, respectively; and HR = 2.39, P = 0.02).…”
Section: Multivariate Analysis On Recurrence and Survival Of Patientsmentioning
confidence: 99%
“…TACE is an effective treatment in patients with unresectable HCC, however most patients treated with TACE will need repeat therapy due to partial response or tumor recurrence. Treatment outcomes after TACE depend on both the severity of underlying liver dysfunction and tumor burden (34). In our study, pre-transplant PIVKA-II levels correlated with the number of TACEs performed prior to pre-transplant sampling.…”
Section: Discussionmentioning
confidence: 54%
“…Data regarding the significant role of the dynamic changes of AFP following TACE were published previously not only in liver transplant patients but also in those where LRT was applied as a first-line treatment. In their study, Mishra et al showed that patients with AFP < 200 ng/mL before and after the first TACE had a better prognosis compared with those with an initial AFP ≥ 200 ng/mL or progressing beyond this threshold after the first procedure (p = 0.0001, [29]). Similarly, other authors have also revealed a positive correlation between AFP response and better long-term results.…”
Section: Discussionmentioning
confidence: 98%